Correlates of e-cigarette use for smoking cessation among clients in residential substance use disorder treatment. (August 2021) - Masson, Carmen L.; Le, Thao; Hosakote, Sindhushree; Fokuo, J. Konadu; Gubner, Noah R.; Shingle, Mallory; Guydish, Joseph
Highlights: Examined correlates of using e-cigarettes to quit smoking in SUD treatment clients. Those with mental health needs were more likely to use e-cigarettes to quit smoking. Harm perceptions were strong predictors of e-cigarette use for quitting smoking. Dual e-cigarette and tobacco cigarette use was higher than other clinical samples. Discuss clinical implications of e-cigarettes as a smoking cessation aid. Abstract: Little is known about e-cigarette use among persons in substance use disorder (SUD) treatment, or their use of e-cigarettes for smoking cessation. Prevalence of e-cigarette use and correlates of e-cigarette use for smoking cessation were examined among clients in SUD treatment. Participants (n = 332) were current cigarette smokers recruited from 20 residential SUD programs in California. We used multivariable logistic regression to identify correlates of using e-cigarettes for quitting smoking. Almost half (45.2%) of the sample had ever used e-cigarettes for smoking cessation, and 34% had used e-cigarettes in the past 30 days. Smokers who had used e-cigarettes for smoking cessation, compared to those who had not, were younger (adjusted odds ratio [AOR] = 0.94, 95% confidence interval [CI] = 0.91, 0.96), had more than a high school education (AOR = 1.69, 95% CI = 1.07, 2.68), sought treatment for both SUD and mental health disorder (AOR = 2.62, 95% CI = 1.38, 5.00), wanted help quitting smoking (AOR = 1.90, 95% CI = 1.03, 3.50) and perceived e-cigarettes as equally harmful (AOR = 3.03, 95% CI = 1.10, 8.33) or less harmful than tobacco cigarettes (AOR = 2.82, 95% CI = 1.02, 7.77). Black/African American and Hispanic/Latino participants were less likely to use e-cigarettes for smoking cessation than participants who identify as White. E-cigarettes were favorably perceived by clients in residential SUD treatment as a quit smoking aid. Treatment programs should consider how to advise clients with respect to the use of e-cigarettes for smoking cessation.